Sense of Community in Graduate Online Education: Contribution of Learner to Learner Interaction - Shackelford, Jo L.; Maxwell, Marge (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
Distance learning technologies offer a multitude of ways to build interaction into online courses to support learning. Based on social constructivism theory, this study explored which types of interaction are most predictive of students’ sense of community in online graduate courses at a regional comprehensive university. Surveys were used to measure sense of community and the frequency and importance of nine learner–learner interactions. Interactions that were most predictive of sense of community were introductions, collaborative group projects, sharing personal experiences, entire class discussions, and exchanging resources. The interaction that offered the highest payoff to instructors was exchanging resources. The article discusses implications for online course design.